Present imperfect imagining utopia. (Lincolnwood, Ill. National Textbook Co., 1999)
Presents three annotated works of utopian science fiction--"The Roads Must Roll," "Herland," and "The Republic of the Southern Cross"--and a section of related articles with discussion questions.
Keywords: Readers (Secondary); Science fiction -- Problems, exercises, etc; Utopias -- Problems, exercises, etc; Readers -- Science fiction; Readers -- Utopias